Critical Illness Neuromyopathy Complicating Akinetic Crisis in Parkinsonism. Issue 28 (July 2015) - Capasso, Margherita; De Angelis, Maria Vittoria; Di Muzio, Antonio; Anzellotti, Francesca; Bonanni, Laura; Thomas, Astrid; Onofrj, Marco; Yong., Li
<x xml:space="preserve">Abstract</x> Abstract Akinetic crisis (AC) is a life-threatening complication of parkinsonism characterized by an acute severe akinetic-hypertonic state, consciousness disturbance, hyperthermia, and muscle enzymes elevation. Injectable dopaminomimetic drugs, high-dose methylprednisolone, and dantrolene are advocated as putative specific treatments. The course of the illness is frequently complicated by infections, pulmonary embolism, renal failure, disseminated intravascular coagulation, and cardiac arrhythmias. Critical illness neuromyopathy (CINM) is an acquired neuromuscular disorder characterized by flaccid quadriparesis and muscle enzyme elevation, often occurring in intensive care units and primarily associated with inactivity, sepsis, multiorgan failure, neuromuscular blocking agents, and steroid treatment. In 3 parkinsonian patients, during the course of AC we observed disappearance of rigidity but persistent hypoactivity. In all, neurological examination showed quadriparesis with loss of tendon reflexes and laboratory investigation disclosed a second peak of muscle enzymes elevation, following the first increment due to AC. Electrophysiological studies showed absent or reduced sensory nerve action potentials and compound muscular action potentials, myopathic changes, and fibrillation potentials at electromyography recordings, and reduced excitability or inexcitability of tibialis anterior at direct muscle stimulation, leading to a diagnosis of CINM in all 3 patients. In 1 patient, the diagnosis was also confirmed by muscle biopsy. Outcome was fatal in 2 of the 3 patients. Although AC is associated with most of the known risk factors for CINM, the cooccurrence of the 2 disorders may be difficult to recognize and has never been reported. We found that CINM can occur as a severe complication of AC, and should be suspected when hypertonia-rigidity subsides despite persistent akinesia. Strict monitoring of muscle enzyme levels may help diagnosis. This finding addresses possible caveats in the use of putative treatments for AC.